Lilium sealyi Y.D.Gao, a new name for Lilium farreri (W.E.Evans) Y.D.Gao - Gao, Yundong; Gao, Xinfen (Phytotaxa, 2020)
Following evidence from morphology and molecular phylogenies, we integrated Nomocharis Franchet (1889: 113) into Lilium Linnaeus (1753: 302) and made the combination L. farreri (W.E.Evans) Y.D.Gao in Gao & Gao (2016: 207) based on Nomocharis farreri (W.E.Evans 1925: 20) Harrow (1928: 76). Unfortunately, this combination in Lilium was blocked by L. farreri Turrill (1919: 76), which is regarded as a synonym of L. duchartrei Franchet (1887: 90). Here we propose a new name to replace the illegitimate name L. farreri (W.E.Evans) Y.D.Gao.